Neutrophils do not contribute to local tissue damage, but play a key role in skeletal muscle regeneration, in mice injected with Bothrops asper snake venom - Teixeira, Catarina de Fátima (2003)
Local tissue damage induced by crotaline snake venoms includes edema, myonecrosis, hemorrhage, and an inflammatory response associated with a prominent cellular infiltrate. The role of neutrophils in the local tissue damage induced by Bothrops asper snake venom and by myotoxin I, a phospholipase A2 isolated from this venom, was investigated. Male Swiss mice were pretreated with either an antimouse granulocyte rat monoclonal immunoglobulin G (IgG) antibody or with isotype-matched control antibody. No significant differences in these local effects were observed between mice pretreated with antigranulocyte antibodies and those receiving control IgG. Moreover, myotoxicity induced by B. asper myotoxin I was similar in neutrophil-depleted and control mice. The role of neutrophils in the process of skeletal muscle regeneration was also assessed. Muscle regeneration was assessed by quantifying the muscle levels of creatine kinase and by morphometric histological analysis of the area comprised by regenerating cells in damaged regions of skeletal muscle. Mice depleted of neutrophils and then injected with B. asper venom showed a more deficient regenerative response than mice pretreated with control IgG. Moreover, a drastic difference in the regenerative response was observed in mice injected with myotoxin I, because animals pretreated with control IgG showed a successful regeneration, whereas those depleted of neutrophils had abundant areas of necrotic tissue that had not been removed 7 days after injection, associated with reduced contents of creatine kinase. It is concluded that (1) neutrophils do not play a significant role in the acute local pathological alterations induced by the venom of B. asper, and (2) neutrophils play a prominent role in the process of skeletal muscle regeneration after injection of B. asper venom and myotoxin I, probably related to the phagocytosis of necrotic material and the recruitment of other inflammatory cells, two events directly associated with a successful muscle regenerative response